Investigating The Determinants of Muslim Intention to Accelerate Zakat Payment During The Covid19 Pandemic - Mujahidah, Anisa Syahidah; Akbar, Nashr (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2022)
The crisis caused by the COVID-19 pandemic is more severe than other crises that have occurred before such as the crisis in 2008. This is because of the speed and scale it has created. The purpose of this study was to determine the effects of the COVID-19 pandemic crisis on changes in the behavior of Muslims in Indonesia, namely accelerating the payment of zakat during the Covid-19 pandemic. The data used in this study is primary data, where data were collected through questionnaires to respondents who were selected purposively throughout the big islands of Indonesia and collected as many as 256 respondents. By using the Structural Equation Modeling (SEM) Partial Least Square approach, it is found that several variables have an influence on the behavior of Muslims to accelerate paying zakat, including the Attitude variable and the Perceived Behavioral Control variable. However, it was found that the Subjective Norm variable was not proven to significantly influence the behavior of Indonesian Muslims to accelerate paying zakat during the COVID-19 pandemic crisis. The limitations of this study are that the sample that dominates is only from the island of Java and the age proportion of the respondents is dominated by millennials and generation z.